Upaya Eliminasi Residu Logam Berat pada Sapi Potong yang Berasal Dari Lokasi Tempat Pembuangan Akhir Sampah dengan Pemeliharaan Secara Konvensional - Sudiyono, Sudiyono (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2011)
The study aimed to determine content of heavy metals Pb and Hg in the organic waste and method to eliminate the heavy metal residue of Pb from beef cattle products, meat and visceral organs. Two male Ongole Crossbred cattles were used in this study. Rations were given in the form of King Grass forage and commercial concentrate of Nutrifeed. The animals were kept for 3 months. At the beginning of the experiment, the fecal and blood samples were collected, then these samples were taken every two weeks. At the end of the experiment, the animals were slaughtered and meat samples of bicept femoris, liver, kidneys and intestines were taken to analyze its Pb content. The results showed that the organic waste contaminated with Pb, but not contaminated with Hg. Pb levels in blood and feces varied and quite high, whereas in beef products, meat and viscera the Pb were quite high and still above the safe limit for consumption. The conclusions of this experiment were that the conventional maintenance for three months after removed from the landfill was not able to eliminate the Pb content in products of beef cattle.